Design modification and finite element analysis of stainless steel 316L locking compression plates for mid-transverse fractures / Muhammad Naufal Nazeri ... [et al.] - Nazeri, Muhammad Naufal; Shuib, Solehuddin; Romli, Ahmad Zafir; Mohd Miswan, Mohd Fairudz (UiTM Press, 2024)
Bone fracture is the most common orthopedics problem. To achieve stability in the internal fixation of bone fragments, apply a Locking Compression Plate (LCP), which consists of a set of plates and screws. Common materials used for the bone fixation plate are stainless steel, titanium, and other metal alloys. Those materials are stiffer than cortical bone, causing a stress shielding effect. The stress shielding phenomenon takes place during bone remodelling, which affects the growth of bone and bone loss upon the healing process. The purpose of this study is to design the best LCP to minimize or eliminate the stress shielding issue for tibia shaft fracture. A reverse engineering process is used to obtain the solid part using 3D scanning, and data clean-up is done in CATIA V5, which is then used to be imported into the finite element software ANSYS 23R2. The fracture simulation is on transverse type fractures with the creation of a gap of 1 mm around the mid-tibial shaft region. Several boundary conditions will be parametrized, such as material properties, contact definitions, meshing, and loading conditions in preprocessing. This paper examines and simulates the behaviour of LCP under a load via finite element analysis (FEA).